2018
DOI: 10.1002/slct.201801288
|View full text |Cite
|
Sign up to set email alerts
|

GFP Chromophores from L‐Phenylalanine: Synthesis, Photophysical and Thermal Properties

Abstract: Synthesis of p-conjugated green fluorescent protein chromophores analogs derived from amino acids are established. Indole and p-nitrophenyl tethered derivatives as the main structure could improve the thermal stability and optical property of the materials. The chromophores show good solubility in MeOH and CH 3 CN. They also show good thermal stability for practical applications. These compounds showed steady green light emissions in the range of 524-578 nm in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Indium trichloride (InCl 3 ) has been widely used in organic transformations for the construction of complex heterocycles [29][30][31]. In continuation of our efforts on exploring the catalytic potential of InCl 3 for the synthesis of novel N-heterocycles [32][33][34], we herein report the InCl 3 -mediated efficient synthesis and the optical characterization of new 2,4-disubstituted quinoline derivatives having potential application as dyes in organic electronic devices (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Indium trichloride (InCl 3 ) has been widely used in organic transformations for the construction of complex heterocycles [29][30][31]. In continuation of our efforts on exploring the catalytic potential of InCl 3 for the synthesis of novel N-heterocycles [32][33][34], we herein report the InCl 3 -mediated efficient synthesis and the optical characterization of new 2,4-disubstituted quinoline derivatives having potential application as dyes in organic electronic devices (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that ESPT [35] or in certain cases, excited‐state intramolecular proton transfer (ESIPT) [36] and internal charge transfer (ICT) [31] may also play an essential role in determining the fluorescence properties of the planar GFP‐like chromophores. Many orthogonal structural modifications of p ‐HOBDI can be found in the literature, also aiming to improve the fluorescence property [37–44] . Alongside the synthetic efforts, an accurate understanding of the fluorescence mechanism must be pursued in order to successfully develop and apply novel fluorophores.…”
Section: Introductionmentioning
confidence: 99%